A SOCIOLOGRAPHIC APPROACH TO THE METHODOLOGY OF TEACHING THE SOCIAL SCIENCES IN UZBEKISTAN - Yunusov, Kamaldin (Journal of Fundamental Studies, 2026)
The purpose of this article is to analyze the methodology of social and humanitarian sciences taught in Uzbekistan through a sociolographic approach and to identify its theoretical and methodological potential. The study employs sociolographic and dialectical approaches, as well as systemic and comparative analysis and content analysis methods. The findings demonstrate that sociolography functions as a significant theoretical and methodological framework that both evaluates and guides the development of the social sciences. It enables the assessment of the social effectiveness, practical relevance, and societal applicability of scientific research. The study also substantiates the persistence of outdated methodological paradigms within the social sciences and highlights the necessity of their renewal. Furthermore, particular emphasis is placed on the importance of methodological pluralism, democratic principles, and the concept of civil society as foundational elements. In conclusion, the sociolographic approach is justified as an essential scientific instrument for advancing and refining the methodology of the social and humanitarian sciences.